Experimental and computational studies of shock wave-to-bubbly water momentum transfer. (June 2017) - Frolov, S.M.; Avdeev, K.A.; Aksenov, V.S.; Borisov, A.A.; Frolov, F.S.; Shamshin, I.O.; Tukhvatullina, R.R.; Basara, B.; Edelbauer, W.; Pachler, K.
Highlights: We have measured and calculated the momentum transfer from the air shock wave to bubbly water implying the use of shock-induced motion of water in advanced pulsed detonation hydrojet engines. Experiments in a hydroshock tube and 2D calculations show that as the initial gas volume fraction in water increases from 0 to 0.3 the momentum imparted in bubbly water by shock waves increases monotonically, gradually levelling off at an air volume fraction of about 0.30. The momentum transfer efficiency at a gas volume fraction of 0.3 attains the values of 12–15% and 20% for weak and strong shock waves, respectively. Abstract: Momentum transfer from shock waves (SWs) of various intensity (from 0.05 MPa to 0.5 MPa in amplitude) to water containing air bubbles 2.5 to 4 mm of mean diameter is studied both experimentally and by means of numerical simulation. Experiments are performed in a vertical shock tube of a 50 × 100 mm 2 rectangular cross section consisting of a 495-mm long high-pressure section (HPS), 495-mm long low-pressure section (LPS), and 990 mm long test section (TS) equipped with an air bubbler and filled with water. Experiments have shown that as the initial gas volume fraction in water increases from 0 to 0.3 the momentum imparted in bubbly water by SWs increases monotonically, gradually levelling off at an air volume fraction of about 0.30. The experimental data are confirmed by two-dimensional (2D) simulation of SW propagation in bubbly water in terms of the SW velocity versus the air content, pressure profiles, as well as liquid and gas velocity behind the shock front.